Past, Present and Future Strategies of Immunotherapy in Gynecological Malignancies - Bellati, F.; Napoletano, C.; Ruscito, I.; Visconti, V.; Antonilli, M.; Gasparri, M.L.; Zizzari, I.G.; Rahimi, H.; Palaia, I.; Rughetti, A.; Benedetti Panici, P.; Nuti, M. (Current Molecular Medicine, 2013)
Recently, the combining of different drugs has greatly improved response and survival rates in gynecological malignancies. Results are however far from being satisfactory. Treatments used in case of advanced or recurrent disease offer limited results in terms of long-term responses. The urgent need for new and more effective treatments has prompted researchers to investigate and propose new therapeutic strategies. One of the most interesting approaches that are being explored is constituted by immunotherapy. Currently, immunotherapeutic strategies include vaccination with peptide, viral vectors, carbohydrates and antiidiotypic antibodies. In addition, cell based immunotherapy has been adopted in vitro activated lymphocytes and dendritic cells. Most experience has been acquired in ovarian cancer and cervical cancer. Little has been investigated in endometrial and rare gynecologic neoplasms. The clinical experiences and results achieved with immunotherapy in this setting of patients have been reviewed and the future avenues that are currently being explored have also been discussed.
Keywords: gynecological cancer